Clinical and Laboratory Aspects of Thyroglobulin and Thyroglobulin Antibody in Differentiated Thyroid Carcinoma - Hani Ajrina Zulkeflee; Tuan Salwani Tuan Ismail; Noorazliyana Shafii (Prince of Songkla University, 2024)
Indexed by Scopus